Competition and optimistic advice of financial analysts: Evidence from IPOs - Sette, Enrico (Journal of Financial Intermediation, 2011)
This paper investigates whether competition affects the degree of optimism in recommendations on Initial Public Offerings (IPOs) issued by affiliated sell-side analysts. Competition is measured by the number of unaffiliated analysts covering the IPO. Since the measure of competition is likely to be endogenous, it is instrumented using the number of analysts who cover stocks in the same industry as the IPO, one quarter before the one in which the recommendation is issued. The results show that affiliated analysts issue less optimistic recommendations when more unaffiliated analysts cover the IPO, suggesting that competition has a causal effect in mitigating the incentives of affiliated analysts to issue favorable investment recommendations. The paper also shows that recommendations issued by analysts affiliated with co-managers of the IPO are significantly less optimistic than those issued by analysts affiliated with the lead underwriter, and that competition affects only the degree of optimism of the latter.